2014
DOI: 10.1016/j.jsams.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of high responders for interleukin-6 and creatine kinase following acute eccentric resistance exercise in elderly obese women

Abstract: "Identification of high responders for interleukin-6 and creatine kinase following acute eccentric resistance exercise in elderly obese women" (2014). Faculty Research and Creative Activity. 35.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
0
34
0
2
Order By: Relevance
“…In addition, Machado and Willardson (2010) reported that an accepted definition of HR and LR currently does not exist in the literature, and that the mechanisms responsible for the disproportionate response in HR are not clearly understood. In fact, motivated by this finding, our research group reported that elderly individuals classified as HR experienced greater CK and interleukin-6 responses to an acute eccentric resistance exercise session (consisting of seven sets of 10 repetitions at 110 % of 10RM, with 3-min rest intervals between sets) (Tajra et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Machado and Willardson (2010) reported that an accepted definition of HR and LR currently does not exist in the literature, and that the mechanisms responsible for the disproportionate response in HR are not clearly understood. In fact, motivated by this finding, our research group reported that elderly individuals classified as HR experienced greater CK and interleukin-6 responses to an acute eccentric resistance exercise session (consisting of seven sets of 10 repetitions at 110 % of 10RM, with 3-min rest intervals between sets) (Tajra et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This might explain why despite increments in muscle strength, some studies did not observe significant effects of RT on circulating BDNF (Levinger et al 2008). This is a relevant topic, because results of studies are normally discussed at the basis of group means and not by classification of responders and nonresponders, which may lead to a misleading interpretation of results (Tajra et al 2014;Garcia et al 2014;Loenneke et al 2014). Even though the presence of high and low responders should receive attention, it is not known whether such individuals can be detected for other important mediators, such as irisin, TLR-4, IL1-β, and BDNF, which play important roles in insulin resistance, inflammation, obesity (Oliveira et al 2011;Pardo et al 2014), and neuroplasticity of the brain (Coelho et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This reinforces the importance of ERE in initial resistance training routines in older adults with low levels of strength and a sedentary lifestyle (Roig et al ., ; Raj et al ., ). Interestingly, higher values of creatine kinase (CK, 361 U l −1 ) have been reported following the same ERE protocol, denoting no alarming CK responses, which could be associated with excessive muscle damage and acute rhabdomyolysis (Tajra et al ., ). ERE was chosen in the current investigation because the reserve of eccentric strength could be used, in combination with a greater magnitude of force development, allowing for a higher training intensity thus maximizing gains in muscle function in elderly subjects (Roig et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Seven days following the 10 RM tests, subjects completed an ERE protocol as previously described (Funghetto et al ., ; Tajra et al ., ). Upon arrival to the lab, subjects began with a warm‐up on a cycle ergometer for 10 min at 60 rpm and 50 W, followed by 10 leg extension repetitions at 50% of 10 RM load, and then a rest interval of 3–5 min was allowed.…”
Section: Methodsmentioning
confidence: 97%
“…Interestingly, elderly subjects preserve eccentric strength as compared with concentric strength, while an eccentric protocol induces lower perceived exertion and metabolic stress versus conventional resistance exercise [11], and induces no alarming creatine kinase (CK) responses in obese elderly women [11]. Changes in serum CK concentration has been previously used as an indicator of muscular damage [12], and is still used in recent studies [13].…”
Section: Introductionmentioning
confidence: 99%